Sediment transport in rigid bed rectangular channel with no deposition / Norhaliza Mat Daut - Mat Daut, Norhaliza (1993)
This project is based on the experimental investigations of sediment transport in fixed bed channels. It attempts to analyse the bedload transports of non-cohesive sediments in fixed bed channel with no deposition. By using these new data as well as previously available data, comparison are made to find the differences in previously work and to advanced the understanding of the processes involved. The results of this analysis are compared with the result obtained by Novak and Nalluri for bedload transport equation in fixed bed channel of rectangular section. The experiments were carried out at the Hydraulics Laboratory of Civil Engineering Department, MARA Institute Of Technology, Shah Alam, Malaysia.